INTEGRASI TEKNOLOGI INFORMASI DALAM PEMBELAJARAN ANAK USIA DINI - Widyawati, Widyawati (EDUCHILD (Journal of Early Childhood Education), 2019)
Early childhood is a golden age period. At this age the development period is observed. Learning media will help the effectiveness of the learning process in delivering messages and contents. Sometimes teachers ignore the use of learning media, whereas information technology tools in learning media, especially audio – visual media, can be applied. Utilization of IT aimed to motivate children in learning that can be easily understood by them. The following steps by using audio visual media in teaching are: preparing a notebook, projector, sound system, cable, video presentation, and the important thing is paying attention to the students’ sitting position in a comfortable state and allowing them to pay attention to the video. The teacher conveys the learning objectives and learning techniques, then students watch the show. After that, students will be given a follow-up in the form of questions related to the video content. Keywords: Learning process, IT, and early childhood